Use of Synchronized AUTOSAR for Adaptive Real Time Scheduling of Distributed Systems - Arya, Mayank (My University, 2015)
An automotive system may comprise of a distributed ECU system. The tasks can be distributed over different nodes in the network. The distributed tasks on different nodes may communicate with each other. Thus the synchronization of these distributed tasks is an important constraint for automotive software development. Moreover, the growing number of ECU’s inside the vehicle has lead to an increase in demands for bandwidth and a need for high level of fault tolerance[1] in the communication network. In order to facilitate ECU software development, a group of automobile manufacturers, suppliers and tool developers have specified a standardized automobile software, AUTOSAR (Automotive Open System Architecture)[2]. Also noteworthy is the point that implementation of such a system adhering to an open standardized automotive software architecture, such as an AUTOSAR greatly increases the usage of the design. Besides the motivation of usability of the implemented system, the specification of AUTOSAR suggests several operating system level features which can be utilized to synchronize the task execution to a global time base of the network. In context to it, the choice of communication standard deployed for a distributed network is also an important factor of consideration. One such communication protocol is the Flexray protocol[3] that supports clock synchronization mechanism for the local clocks at the nodes in the network to a calculated global time base. Apart from it the Flexray communication architecture is time deterministic, fault tolerant and offers a higher bus bandwidth compared to the existing communication protocols such as a CAN[4] or a LIN[5]. The realisation of such a system that supports adaptive clock synchronization during run time is implemented in ARCTIC Studio[6] environment. The ARCTIC Studio environment supports a C development environment that supports module plug-ins to facilitate efficient development of AUTOSAR solutions. The layered software AUTOSAR architecture comprising of all the necessary modules can be integrated with a Flexray communication stack to implement the system. The testing of such a system is performed using simulators and debug analyzers, to ensure that all timing properties are fulfilled.
Keywords: Data- och informationsvetenskap; Computer and Information Science